Why Nonunion Representation Is Legal in Canada - Taras, Daphne (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1997)
This study examines the factors which led to the continued legality of nonunion collective representation in Canada, in contrast to the American approach which banned formal nonunion plans. It is argued that the delay in the passage of Canadian labour laws allowed a constellation of pressures to emerge which supported the continued use of nonunion plans within both private and public sectors. Further, the influence of William Lyon Mackenzie King, and his prior support for a particular nonunion approach were influential in Canada. Canadian statutory mechanisms and subsequent labour board interpretations are presented. The practical result is that nonunion plans continue to persist outside of the statutory regimes governing union-management relations, and may form an important component of the industrial relations landscape.